The Relative Importance of Language in Guiding Social Preferences Through Development - Esseily, Rana; Somogyi, Eszter; Guellai, Bahia (Frontiers in Psychology, 2016)
In this paper, we review evidence from infants, toddlers, and preschoolers to tackle the question of how individuals orient preferences and actions toward social partners and how these preferences change over development. We aim at emphasizing the importance of language in guiding categorization relatively to other cues such as age, race and gender. We discuss the importance of language as part of a communication system that orients infants and older children’s attention toward relevant information in their environment and toward affiliated social partners who are potential sources of knowledge. We argue that other cues (visually perceptible features) are less reliable in informing individuals whether others share a common knowledge and whether they can be source of information.